KINERJA DOSEN DAN PENGARUHNYA DALAM MEMOTIVASI MINAT BELAJAR MAHASISWA - Fadil Iskandar (Universitas Batanghari Jambi, 2015)
This research is about the influence of Lecturer Performance toward Student’s Learning Interest. The aim of this research is to find out about is it true that lecture performance influence students learning interest. In order to find it out, the highlight of this research is lecturer performance which includes phisically lecturer performance, lecturer knowledge about the subject which he or she going to explain, lecturer behaviour on the way he or she teaching, intrinsic motivation and extrinsic motivation.This research is using questionnaire to measure student interest and also observation form to find out lecturer performance, in order to collect the data. The data collection is taken at the Faculty of Economics, Management Department of Batanghari University at the even semester, year 2014/2015, student year of 2009 through 2014 which is still active academically, and also guest lecturers, senior lecturer, junior lecturer who give lecture at Batanghari University, specially at the Faculty of Economics, Management Department. This research is using multiple linier regression methods. This research show that the lecturer performance do not influence students interest but the influence factor are intrinsic motivation and extrinsic motivationKey Word: lecturer performance, intrinsic motivation and extrinsic motivation